Agentes verossímeis: uma investigação sobre a construção dos personagens autônomos nos videogames - Gomes, Renata Correia Lima Ferreira (2008)
From the conceptual of character-oriented games and of simulation games the present research draws the idea of narrative games as an immersive simulation , to be experienced by the interactor through his or her traversing the virtual space of the game as an implicated character and through his or her interaction with the autonomous characters of the game. We carry through the hypothesis that the key for the implentation of a dramatic strutucture in the game albeit fundamentally different from that of film or theater is in the design of autonomous characters. These we take to be object inhabiting the space-time of the game, carrying a high degree of autonomy, complexity and intentionality, who, through the possibility of empathy, constitute in themselves a pathway towards a dramatic entity with or against whom the interactor has to act. To demonstrate that, we describe narrative as a evolutionary strategy towards a causal mindframe, which evolves side-be-side with the media that materialize it, from oral narratives to 3D interactive digital pieces. A second step toward demonstrating our hypothesis is to describe autonomous characters through Artificial Intelligence applied to narrative: the believable characters . We take as a reference the work of the research groups Oz and Synthetic Characters, and of Brazilian game designer Marcos Cuzziol. Finally, a third step is to approach the nature of the fiction character, through the work of Aristotle and Fernando Segolin, and the concept of empathy, under the approach of Evan Thompson. Empathy here is understood as pre-condition for the comprehension of the Other and of ourselves as affective, emotional and intentional entities. To illustrate this final view, we analyze a few aspects of the Creatures from the games Black & White I e II, in an attempt to point out how some qualities proposed are instantiated